Turkish studies in the history and philosophy of science - Irzik, Gürol. (Boston studies in the philosophy of science, 2005)
The present book, which contains seventeen newly commissioned articles, aims to give a rich overview of the current state of research by Turkish philosophers and historians of science. Topics covered address issues in methodology, causation, and reduction, and include philosophy of logic and physics, philosophy of psychology and language, and Ottoman science studies. The book also contains un unpublished interview with Maria Reichenbach, Hans Reichenbach's wife, which sheds new light on Reichenbach's academic and personal life in Istanbul and at UCLA. This volume is primarily intended for researchers in the philosophy and history of science. However, it should also be valuable to other philosophers working in fields such as epistemology, metaphysics, philosophy of mind, and philosophy of language, as well as to physicists, cognitive scientists and liguists interested in philosophical issues. "Philosophy is alive and well in Turkey. This is a wonderful volume, chock-full of first-rate essay by Turkish philosophers and historians of science. Readers will also learn something about the early days of analytical philosophy in Turkey. The interview that Güven Güzeldere conducted with Maria Reichenbach and David Kaplan is a fascinating read. If, however, your department is fighting for more office space, keep the volume out of the hands of your university administrators. Maria Reichenbach reports: `Hans by the way shared an office with Bertrand Russell when he was at UCLA'." Brian McLaughlin, Professor and Chair, Philosophy Department, Rutgers University. Philosophy of formal and physical sciences -- Demarcation of the logical constants and logical truth in terms of analyticity -- General theory of relativity and the 5th test -- Implications of the geometry of quantum mechanical perfect correlation functions concerning “bell’s theorem without inequalities” -- Introductory remarks -- Epistemological and methodological issues in science -- Quine’s robust relativism -- Confirmation of theoretical hypotheses: bootstrapping with a bayesian face -- Idealizations and approximations in science, and the bayesian theory of confirmation -- Repeated independent discovery and ‘objective evidence’ in science: an example from geology -- A study on the heuristic of saccheri’s Euclides -- An Interview with Maria Reichenbach and David Kaplan -- Philosophy of language and mind -- Discovery and inostensible de re knowledge -- Implications of the distinction between semantics and pragmatics for philosophy of science -- Computation and functionalism: syntactic theory of mind revisited -- Causes and action -- Causation, parts and properties -- Causal relations in hume -- How causes can rationalize: belief-desire explanations of action -- Ottoman science studies -- Ottoman science studies-A review -- Institutionalisation of Science in the medreses of pre-ottoman and ottoman turkey -- Late ottoman and early republican science periodicals.